Ressonâncias do fantástico: um estudo interartes de “O jardim das delícias terrenas”. - Corrêa, Camilla da Silva (2019)
The present study proposes an Inter art's analysis of the triptych "The Garden of Earthly Delights" (1503-1515), by Hieronymus Bosch, based on the literary theories of the Fantastic. Although we can maintain that the referred canvas has elements that allow us to consider it an aesthetic work belonging to the Fantastic, the present thesis does not have the objective of proposing a new concept for the aesthetics abovementioned, considering the fact that Bosch's work is much earlier than the classification of fantastic literary. Here, we intend to outline an analysis from the transposition of a common aesthetic concept from the literature to the plastic arts, based on the interdisciplinary look of the Inter art and Cultural Studies, the fruition and The Open Work developed by Umberto Eco. This study will be organized following this order, first, it will be on the discussion around the Fantastic, starting from Todorov's seminal essay and extending the debate to other thinkers, as well as their relationship with similar genres. We consider that Boschian art can be seen as a pictorial text of a hybrid nature, which requires the knowledge of a broad aesthetic context that goes beyond Todorov's traditional perspective. Subsequently, we will establish a parallel between Bosch's work and later literary works, such as Vax, Caillois, Bessière, Jackson, Freud , Ceserani and others, in order to understand the Fantastic as a timeless aesthetic and current in many forms of artistic expression. The analysis of Bosch's painting in conjunction with the literary texts mentioned above will allow us to better understand a complex aesthetic phenomenon and closely related to literature and to the visual arts and still debated far too little. Keywords: Inter art Studies, Fantastic Art, Hieronymus Bosch